Bilateral Angle Closure Following the Infusion of a Monoclonal Antibody to Treat Relapsing Multiple Myeloma. Issue 9 (September 2018) - Lee, Andrew C.; Greaves, Giovanni; Lee, Ruby; Zdravkova, Maria; Ahmad, Samrah; McGovern, Kerri; Ghiuzeli, Cristina; Hymowitz, Maggie
Abstract : Purpose: We describe a case of bilateral angle closure glaucoma following the infusion of daratumumab, a monoclonal antibody used to treat relapsing multiple myeloma. Methods: This is an interventional case report. Results: A 59-year-old woman presented with bilateral angle closure glaucoma one day following her first infusion of daratumumab. B-scan echography showed ciliochoroidal effusions in both eyes. Cycloplegia was implemented given the suspicion for drug-induced angle closure, which resulted in prompt deepening of the anterior chambers and normalization of intraocular pressures. The ciliochoroidal effusions resolved 16 days following the cessation of daratumumab. Conclusions: Daratumumab may be associated with drug-induced secondary angle closure glaucoma.